Photobiodegradation of reactive black 5 (RB5) using aspergillus niger and N,S-TiO₂ under visible light - Borhan, Nurwanim (2016)
The rate of photodegradation, biodegradation and combined photobiodegradation on reactive black 5 (RB5) using N,S-TiO₂ and Aspergillus niger under visible light has been investigated. Various reaction parameters such as dopant concentration and catalyst loading of N,S-TiO₂ and, inoculum size of Aspergillus niger were investigated. The photocatalyst samples were prepared using solgel method with titanium tetraisopropoxide as precursor of titania. Three different dopant concentrations were investigated; 0.5%, 0.75% and 1.0% while the catalyst loading were varied from 1 g/L, 2 g/L and 3 g/L to determine the optimum condition for the photodegradation of Reactive Black 5. The rate of biodegradation of Reactive Black 5 also was investigated by using Aspergillus niger by varying the inoculum size from 5 ml, 10 ml and 15 ml. From these batch experiment, the optimum dopant concentration 0.75% N,S-TiO₂, catalyst loading 3 g/l and 10 ml of inoculum size were used to investigate the combination of photobiodegradation experiment. In photobiodegradation experiment, the initial Reactive Black 5 concentration was varied; 10 ppm, 25 ppm and 50 ppm to investigate the rate of photobiodegradation with time. The finding shows that the combined photobiodegradation took only 6 hours to degrade 90% of the Reactive Black 5, whereas photodegradation took 7 hours and biodegradation took 72 hours to degrade the Reactive Black 5. This can be concluded that photobiodegradation processes can save more time to degrade the Reactive Black 5.